Feminist data protection: An introduction - Jens T. Theilen; Andreas Baur-Ahrens; Felix Bieker; Regina Ammicht Quinn; Marit Hansen; Gloria González Fuster (Internet Policy Review, 2021)
"Feminist data protection" is not an established term or field of study: data protection discourse is dominated by doctrinal legal and economic positions, and feminist perspectives are few and far between. This editorial introduction summarises a number of recent interventions in the broader fields of data sciences and surveillance studies, then turns to data protection itself and considers how it might be understood, critiqued and possibly reimagined in feminist terms. Finally, the authors return to 'feminist data protection' and the different directions in which it might be further developed-as a feminist approach to data protection, as the protection of feminist data, and as a feminist way of protecting data-and provide an overview of the papers included in the present special issue.
Keywords: 300; Data protection; Privacy; Feminist data protection; Feminism